2020
DOI: 10.1186/s12968-020-00627-x
|View full text |Cite|
|
Sign up to set email alerts
|

Cardiovascular magnetic resonance native T2 and T2* quantitative values for cardiomyopathies and heart transplantations: a systematic review and meta-analysis

Abstract: Background: The clinical application of cardiovascular magnetic resonance (CMR) T 2 and T 2 * mapping is currently limited as ranges for healthy and cardiac diseases are poorly defined. In this meta-analysis we aimed to determine the weighted mean of T 2 and T 2 * mapping values in patients with myocardial infarction (MI), heart transplantation, non-ischemic cardiomyopathies (NICM) and hypertension, and the standardized mean difference (SMD) of each population with healthy controls. Additionally, the variation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 201 publications
(363 reference statements)
2
30
0
1
Order By: Relevance
“…There is also a lack of understanding of how these changes in parameters affect T2 or T2* measurements. Reported T2 and T2* values in healthy subjects showed large variation between centres which could be explained due to the acquisition standardisation 18 . While the literature highlighted some guidelines for use of protocols for T2* measurements for cardiovascular image 19 , different acquisition approaches were implemented for T2 sequences and hence lead to variations in T2 values 20 .…”
Section: Introductionmentioning
confidence: 99%
“…There is also a lack of understanding of how these changes in parameters affect T2 or T2* measurements. Reported T2 and T2* values in healthy subjects showed large variation between centres which could be explained due to the acquisition standardisation 18 . While the literature highlighted some guidelines for use of protocols for T2* measurements for cardiovascular image 19 , different acquisition approaches were implemented for T2 sequences and hence lead to variations in T2 values 20 .…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, a 3D T2 mapping sequence was developed [9] and subsequently evaluated for the detection of the focal hotspots of myocardial injury, specifically those related to ACAR [10]. While the results of the DRAGET trial are pending, a number of studies on multiparametric CMR in HTx were published recently [11][12][13]. Vermes reported that using a combination of a T2 (>57,7 ms) and ECV (>32%) cut-off values for ACAR detection could have prevented 63% of routine biopsies [11].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the assessment of institution-specific reference ranges with established scanner- and sequence-specific T 2 values in healthy volunteers are strongly recommended ( 2 ). With scanner- and sequence-specific reference values as a prerequisite, it was demonstrated that T 2 values in studies of specific inflammatory conditions such as myocarditis ( 3 ), systemic sclerosis ( 37 ), and sarcoidosis ( 35 ) can unequivocally be used to identify myocardial injury. Therefore, the significant difference in T 2 relaxation time that was found in patients using the 3D but not the 2D T 2 mapping merits special attention, as this might suggest better sensitivity to detect tissue alterations with the proposed high-resolution motion-registered radial 3D T 2 mapping technique at 1.5T.…”
Section: Discussionmentioning
confidence: 99%